The effects of carabid beetles (Coleoptera: Carabidae) on the arthropod fauna of wheat fields in Chile - Carrillo, R. (2007)
The role of carabid beetles in reducing populations of phytophagous insects has been an elusive subject. A field experiment was established on a commercial wheat crop (cv. Otto) with an area of 4.5 ha in Valdivia, Chile, during the spring and summer of 1996-1997. The field had been under a prairie system for two years, before wheat sowing (fertilization and a pesticide had been applied during crop development). Samples were taken at approximately monthly intervals. Carabid beetles were sampled with a grid of pitfall traps and other insects were sampled with a vacuum insect net and soil cores. The genera of the carabids found are of neotropical origin. Exclusion by polythene barriers, together with removal of carabid beetles using traps, was an effective technique for controlling carabid populations in a commercial wheat crop. A reduction in the number of carabid beetles was associated with an increase in the number of springtails and arachnids, and a decrease of agromyzid adults. Phytophagous insects, such as homopterans and lepidopterous larvae, were not affected by carabid exclusion and removal. The action of carabid beetles on the arthropod fauna can be extremely complex, due to its predatory activity at multitrophic levels.